Empowered by Extremes: Indonesian Women In Jemaah Islamiyah (JI) & Jemaah Ansharut Daulat (JAD) - Permana, Aulya Nanda (Security Intelligence Terrorism Journal (SITJ), 2025)
This study examines the evolving roles of Indonesian women within terrorist networks, focusing on Jemaah Islamiyah (JI) and Jemaah Ansharut Daulah (JAD). Using Moghaddam's Staircase to Terrorism model and Riyanta's shortcut to terrorism model, this study analyzes how women's radicalization progresses through both gradual psychological and ideological processes and accelerated digital exposure. Data were drawn from secondary sources, including academic articles and case studies of Indonesian female extremists. Findings indicate that women's participation has expanded from supportive domestic roles to operational involvement as recruiters, propagandists, financiers, and suicide bombers. Their radicalization is often facilitated by family and marital networks, religious study groups (pengajian), and online propaganda, reflecting both traditional pathways and modern digital acceleration. The study argues that women's involvement in terrorism represents a paradoxical form of empowerment, breaking gender norms while simultaneously reinforcing ideological subjugation. This phenomenon highlights the shifting gender dynamics within extremist movements and emphasizes the importance of gender-sensitive approaches in Indonesia's counter-radicalization and rehabilitation strategies.